Food Safety: Does Your Kitchen Pass the Test? - Jennifer Hillan (EDIS)
FCS8801, a 2-page fact sheet by Jennifer Hillan, offers a food safety quiz that readers can take to find out if their food safety practices "pass the test." Includes information on sanitation, storage, and preparation. Published by the UF Department of Family, Youth and Community Sciences, April 2007.